Mapping seasonal and annual extreme precipitation over the Peruvian Andes - Domínguez-Castro, F. (2018)
Seasonal and annual extreme precipitation over the Peruvian Andes have been mapped for the first time. Maps were developed using the most complete, quality-controlled and homogenous daily precipitation records in Peru from 1973 to 2016. For each observed rain gauge series, we defined parameters as the de-clustered daily intensity, total precipitation duration, total magnitude and dry-spell length. Then, we fitted the seasonal and annual series of these variables to a Generalized-Pareto distribution using a peak-over-threshold approach. We estimated the distribution parameters and validated the performance of different thresholds to obtain the best estimation of precipitation probability. We also mapped the distribution parameters obtained for the different meteorological stations using the universal kriging algorithm, accounting for elevation and the distance to the Pacific Ocean as co-variables. The accuracy of the extreme precipitation maps for a period of 25 and 50 years were validated using a jack-knife approach. Some of the maps show strong uncertainty given the random spatial distribution of the variables as a consequence of the complex topography and climate of the region. Nevertheless, the maps show a useful general assessment of the spatial distribution of the precipitation hazard probability over the region, providing a good agreement with the estimations obtained in the meteorological stations for some variables and time periods analysed. Extreme precipitation maps over this high-complex terrain of Peru are of key importance for flood risk assessment, water resources management, crop yield, soil conservation and human settlements.